Treatment with cimetidine of atypical fasciitis panniculitis syndrome. Issue 10 (October 1990) - Naschitz, J E; Yeshurun, D; Rosner, I; Abrahamson, J E; Misselevitch, I; Boss, J H
Abstract : Three patients presented with septal fasciitis and panniculitis, associated with clinical and laboratory features which precluded straight-forward classification into eosinophilic fasciitis, localised scleroderma, or lupus erythematosus profundus. Treatment with cimetidine caused the remission of cutaneous manifestations and the extracutaneous abnormalities, such as nailfold capillary disturbances and the presence of antithyroid antibodies, improved. It is concluded that features of eosinophilic fasciitis or localised scleroderma and certain additional atypical elements should be categorised as atypical fasciitis-panniculitis syndrome.